The effects of Artemisia deserti ethanolic extract on pathology and function of rat kidney - Ali Noori; Leila Amjad; Fereshteh Yazdani (Mashhad University of Medical Sciences, 2014)
Objectives: Medicinal plants played an important role in human health. The kidney is a major organ for elimination the additional materials of body. Some of metabolic waste products are excreted through the kidneys, give us useful information about kidney health. Therefore, the aim of this research was to study the effects of A. deserti flowering tips extract on kidney. Materials and Methods: Three groups of animal were studied. Wistar rats were divided into three groups. Group 1 was injected with saline, group 2 and 3 were injected with extract, 100 mg/kg and 200 mg/kg, respectively. The animals were anesthetized, blood samples were collected 2 days after the last injection, then urea, uric acid and creatinine levels were assayed. Also, the kidney histology was studied. Results: No significant changes in urea and uric acid were observed. But, creatinine concentration was changed significantly in group 3 compared to other groups. The extract caused histologic changes in the kidney, including, glomerular atrophy, congestion of inflammatory cells and degeneration of the renal tubules. Conclusion: The results showed that A. deserti extract was able to damage the kidney tissue. However, the reason for these histopathological changes remains to be clarified.